2021
DOI: 10.1002/berj.3745
|View full text |Cite
|
Sign up to set email alerts
|

Geographical mobility and children’s non‐completion of upper secondary education in Finland and Germany: Do parental resources matter?

Abstract: It is often assumed that families migrate to improve their economic and social prospects, and that these additional resources can benefit the whole family. However, existing research suggests that many children who have experienced (internal) migration underperform compared to their nonmigrating peers in terms of different socioeconomic outcomes. In this article, we study the effects of geographical mobility on children's non-completion of upper secondary education in Finland and Germany using Finnish register… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 60 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…Previous research has also indicated that residential mobility is associated with more negative educational outcomes (e.g. Pribesh and Downey, 1999;McMullin et al, 2021). In their review of the evidence, Leventhal and Newman (2010) conclude that alongside the findings on housing and health effects, the strongest evidence is for residential mobility having an effect on children's short-term academic outcomes.…”
Section: Residential Mobility and Child Outcomesmentioning
confidence: 97%
“…Previous research has also indicated that residential mobility is associated with more negative educational outcomes (e.g. Pribesh and Downey, 1999;McMullin et al, 2021). In their review of the evidence, Leventhal and Newman (2010) conclude that alongside the findings on housing and health effects, the strongest evidence is for residential mobility having an effect on children's short-term academic outcomes.…”
Section: Residential Mobility and Child Outcomesmentioning
confidence: 97%